ТЕОРЕТИЧНІ ОСНОВИ ОЦІНКИ ДІЙ ЧЛЕНІВ ЕКІПАЖУ В ОСОБЛИВИХ ВИПАДКАХ В ПОЛЬОТІ - Н.І. Кушнєрова; А.В. Гончаренко (Системи озброєння і військова техніка, 2025)
The article explores the problems of the aviation industry with a focus on flight safety. The focus is on crew competence and preparedness to respond to in-flight contingencies. Crew response in such situations plays a key role in minimising the consequences of incidents, highlighting the importance of careful analysis of their behaviour.